The Central American integration process today within the framework of EU-Central American relations - Romero Caballero, Vicente (REVISTA ELECTRONICA IBEROAMERICANA, 2024)
This article aims to analyse the current situation of the Central American integration process, which began in the middle of the last century, within the framework of EU-Central American relations, which have played a key role in supporting the peace processes of the 1980s (Esquipulas), and in supporting the integration process up to the present day, through various initiatives. Thus, the article briefly analyses the Political Dialogue developed by both regions: we will focus on the evolution since the 1980s (San José Dialogues), which promoted the new integration process that had been blocked by the war between El Salvador and Central America in 1969; the regional conflicts of the 1980s; and finally, the evolution of the same in the framework of the Tegucigalpa Protocol and relations around political dialogue, cooperation and trade in the 1990s and the beginning of the century up to the signing of the Association Agreement between the two regions. Finally, the article analyses the current situation, in the context of permanent instability in the Central American region, and possible actions that, from the European Union, could favour the Central American integration process, which, in practice, has been a positive element for the development of a peripheral and underdeveloped region such as Central America.
Keywords: Central America; Integration; European Union; Association Agreement; Political Dialogue; Trade; Cooperation